2017
DOI: 10.18632/oncotarget.20566
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 10A is overexpressed in lung tumor cells and inhibitors selectively suppress growth by blocking β-catenin and MAPK signaling

Abstract: Phosphodiesterase 10A (PDE10) is a cyclic nucleotide (e.g. cGMP) degrading enzyme highly expressed in the brain striatum where it plays an important role in dopaminergic neurotransmission, but has limited expression and no known physiological function outside the central nervous system. Here we report that PDE10 mRNA and protein levels are strongly elevated in human non-small cell lung cancer cells and lung tumors compared with normal human airway epithelial cells and lung tissue, respectively. Genetic silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
2
26
1
Order By: Relevance
“…YL-9, by itself, did not affect the cell proliferation ( Figure S1 ), survival ( Figure 2 and Figure S2 ) and cell cycle progression ( Figure 3 A). The sensitization activity of YL-9 on vinorelbine-induced effect was independent of the suppression of PDE5 because the experiments were performed in NCI-H460, a cell line with low PDE5 expression [ 22 ]. Furthermore, YL-9 displayed equal sensitization activity to sildenafil in vinorelbine-induced effects, although its anti-PDE5 activity was 167 times less than that of sildenafil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YL-9, by itself, did not affect the cell proliferation ( Figure S1 ), survival ( Figure 2 and Figure S2 ) and cell cycle progression ( Figure 3 A). The sensitization activity of YL-9 on vinorelbine-induced effect was independent of the suppression of PDE5 because the experiments were performed in NCI-H460, a cell line with low PDE5 expression [ 22 ]. Furthermore, YL-9 displayed equal sensitization activity to sildenafil in vinorelbine-induced effects, although its anti-PDE5 activity was 167 times less than that of sildenafil.…”
Section: Discussionmentioning
confidence: 99%
“…NCI-H460 is a good cell model in studying anti-NSCLC research as the cells may harbor stem-like cells in readily forming anchorage-independent floating spheres, displaying high proliferative potential [21]. Furthermore, NCI-H460 is the cell line showing the least expression of PDE5 among various NSCLC cell lines [22] and enables the study of PDE5-independent signaling pathways in the present work. YL-9 exhibited similar potency to sildenafil in sensitizing vinorelbine-induced inhibition of cell proliferation in NCI-H460 cells using sulforhodamine B (SRB) assay.…”
Section: Yl-9 Shows Less Anti-pde5 Activity But Reserves Sensitizing mentioning
confidence: 98%
“…Sulindac and its derivatives highlight the involvement of the cGMP/PDE/PKG signaling pathway in cancer. PDE5 promotes tumorigenesis and is overexpressed in tumors of the colon, lung, and breast [95,[238][239][240]. Sulindac sulfide inhibited PDE5, resulting in higher intracellular cGMP levels, thus activating protein kinase G (PKG) [95,96].…”
Section: Phosphodiesterases (Pdes)mentioning
confidence: 99%
“…Recent studies showed that PDE10A expression is upregulated in certain cancer models suggesting that PDE10Amediated signaling is involved in tumor cell growth (Zhu et al 2017). New PDE10A-inhibiting lead compounds that do not cross the blood brain barrier are being developed for cancer treatment (Gary Piazza, South Alabama).…”
Section: Cgmp Pde Structure and Functionmentioning
confidence: 99%